Implementing Relationship Marketing to Enhance Customer Loyalty - Sherlita Andinia Putri; Subiyantoro (Politeknik Negeri Madiun, 2024)
The increasingly intense business competition requires companies to implement marketing strategies that focus not only on transactions but also on long-term relationships with customers. This study aims to describe the implementation of relationship marketing at PT INKA Multi Solusi Trading (PT IMST) Madiun in improving customer loyalty. The research used a qualitative descriptive method, collecting data through interviews with three informants consisting of staff and the junior specialist in the marketing division. The results indicate that PT IMST applies relationship marketing strategies through three main stages: identifying potential customers by analyzing purchase history and offering special deals, developing customer portfolio management by differentiating customers based on profitability and strengthening trust with high-value clients, and maximizing customer equity through maintaining product quality, communication, and service. These strategies effectively strengthen customer relationships and increase long-term loyalty.